Effect of Organic and Non-Programmatic Fertilizers on Tomato Yield - Ismailov Uzakbay Embergenovich; Kosbauliev Maksut (Researchparks Publishing, 2022)
It is important to get a high yield of tomatoes and increase soil productivity in the saline soil conditions of the Republic of Karakalpakstan. In order to determine whether tomatoes can be grown in organic farming, we used organic fertilizer at 20, 40 and 60 t/ha, mineral fertilizer N125 P90 K60 kg/ha, glauconite at 1 t/ha and siderate fertilizers. We conducted a field experiment to determine the efficiency of use. As it is known from the results of the research, the use of organic fertilizer in the amount of 40 and 60 t/ha and additional gluconite in the amount of 1 t/ha in feeding tomatoes ensured the production of 181.2-200.0 c/ha, and only it was 21.0-40.c/c more than when mineral fertilizer was used.